The role of syntax, semantics, and pragmatics in pronoun resolution: A cross-linguistic overview - Israel de la Fuente; Barbara Hemforth; Colonna, Saveria; Schimke, Sarah (Empirical perspectives on anaphor resolution, 2016)
Most psycholinguistic and computational linguistic work done in the field of ref- erence interpretation agrees today that the process of resolving a referring expression consists of several different stages (Kehler 2008 summarizes them with the SMASH algorithm: Search, Match, And Select using Heuristics). Different resoution strategies are assumed to hold for each of the stages. First, comprehenders collect all possible referents available within a given contextual frame. No selection or ranking of referents happens at this stage. Second, these candidates are filtered out through a series of “hard” morphosyntactic constraints, such as number, gender, person, binding constraints, etc. Finally, if more than one candidate remains possible as the antecedent of the referential expression after applying these hard constraints, the appropriate referent is selected based on some combination of “soft” constraints or heuristics (e.g. syntactic function, parallelism, thematic role, etc.). It is important to note, however, that while most psycholinguistic approaches to pronoun resolution have been primarily concerned with identifying these hard and soft constraints, little attention has been paid to providing a detailed and integrated explanation for the observed patterns, and for why different preferences seem to weigh differently in different contexts. Kehler (2008) is an exception to this rule. He explains the different weights of constraints by a combination of strategies based on preferences regarding the production of referential expressions and strategies based on discourse expectations. The goals of this article are twofold: we will give an overview of some cross- linguistic work on pronoun resolution, summarizing results from a variety of off-line and on-line studies. Moreover, based on the observed results, we will suggest that pronoun resolution preferences in a particular language need to be explained by a combination of syntactic, semantic, and pragmatic factors which, crucially, do not play out in the same manner within and across sentences (or better Dis- course Units [DU], as we will argue). We will focus on two factors: the effect of the availability of alternative constructions for a particular interpretation in a lan- guage and the question of whether the pronoun and its antecedent are in the same or in a separate DU. We will relate our results to a de notion of DU by Miltsakaki (2002) and show where this definition falls short of explaining the empirical results. Against these previous definitions of DU that equate this notion to either the sentence or the clause, in the last section of this article, we will provide evidence in favor of a more dynamic multifactorial definition of DU that systematizes and accounts for the preference patterns. We will argue that all the factors to be considered are valid across languages. However, their manifestation depends on the grammar of any particular language.